COLLECTIVIZATION IN KARAKALPAKSTAN AND ITS EFFECTS FOR AULS (VILLAGES) - Ilyasbek Mamatkarimov (Journals Park Publishing, 2022)
The given article discusses the period of collectivization of Karakalpakstan in the late 20s and early 30s of the XX century. The nationalization of the region's resources, land and water policy, which did not give the expected result, but despite their inefficiency, the totalitarian government was increasingly gaining turnover. The reasons for all the failures were declared to be the prosperous population of the villages, bayi (richman), the clergy, mirabs, merchants and local authorities.